The impact of rheumatoid arthritis on perioperative complications and hospitalization costs of lumbar fusion: a national analysis - Ye, Lulu; Geng, Wenyan; Wang, Jian; Tang, Qiuyuan; Yang, Qinfeng; Wang, Qiongxiao; Fang, Gang; Chen, Yuhang; Pang, Yuzhou (Frontiers in Surgery, 2025)
BackgroundSeveral studies have evaluated the influence of rheumatoid arthritis (RA) on postoperative results following lumbar fusion. Nonetheless, there is a lack of national-level data on the hospitalization costs and perioperative complications associated with RA patients who underwent lumbar fusion.MethodsThe Nationwide Inpatient Sample (NIS) database was analyzed from 2011 to 2019, focusing on individuals who received lumbar fusion procedures. Our retrospective study included 282,339 patients identified based on the International Classification of Diseases, Ninth and Tenth Editions (ICD-9/10). A comparative analysis was conducted using the outcomes of 8,993 patients with RA and 273,346 non-RA (NRA) patients. Propensity score matching was performed for the RA vs. NRA patients (1:2) in each procedure group to control for confounding demographic variables.ResultsPatients with RA were notably older on average (64 years vs. 60 years in NRA, P < 0.001) and had a higher proportion of females (P < 0.001). The RA cohort also experienced significantly longer hospital stays (P < 0.001) and higher hospital charges. Regarding perioperative complications, individuals with RA were significantly more likely to develop postoperative anemia (RA 22.2%vs. NRA 18.2%, P < 0.001) and require blood transfusions (RA 11.7% vs. NRA 9.7%, P < 0.001). No significant differences were observed in other recorded inpatient complications between RA and NRA patients.ConclusionDespite longer hospital stays and increased hospital charges, patients with RA did not show an increased risk of most in-hospital complications associated with lumbar fusion during the perioperative phase in the United States, except for postoperative anemia and the requirement for blood transfusions.